The Effect of Problem-Based Learning on Grade XI Students' Creativity in Heat Topics - Puastri Putri, Leza; Gunawan, Gunawan; Busyairi, Ahmad; Taufik, Muhammad (Department of Physics Education, Universitas Mataram, 2024)
This study aims to investigate the influence of the Problem-Based Learning (PBL) model on students' creativity in the topic of heat at SMAN 2 Praya. The study reveals that students' creativity in this topic is still low, caused by a lack of interest in lecture-based learning or other conventional methods. The PBL model, which integrates real-life problems, is expected to help students develop thinking skills and construct their knowledge independently. This research employs a quantitative approach with a quasi-experimental method. The population consists of Phase F, 11th-grade students at SMAN 2 Praya. The sample was selected using purposive sampling, with class F1-1 designated as the control group and class F1-2 as the experimental group. The data collection instrument was an essay test, tested for validity, reliability, difficulty level, and discrimination power. Data analysis was performed through normality, homogeneity, and hypothesis testing using the ANOVA test. The results indicate a significance value of 0.00, suggesting that the PBL model has a significant effect on improving students' creativity. This conclusion supports the implementation of PBL as an effective learning method to enhance students' creativity in the topic of heat.